Resistance to Cucumber Green Mottle Mosaic Virus in Cucumis melo - Leticia Ruiz; Carmelo López; Belén Picó; Dirk Janssen (Plants, 2021)
Cucumber green mottle mosaic virus (CGMMV) is a severe threat to melon production worldwide. At present, there are no cultivars available on the market which show an effective resistance or tolerance to CGMMV infection; only wild Cucumis species were reported as resistant. Germplasm accessions of Cucumis melo, as well as C. anguria, C. ficifolius, C. myriocarpus and C. metuliferus, were mechanically infected with isolates belonging to the European and Asian strain of CGMMV and screened for resistance by scoring symptom severity and comparing the accumulation of virus by qRT-PCR. The wild species C. anguria and C. ficifolius showed no symptoms and did not accumulate CGGMV following inoculation, while C. metuliferus was highly susceptible to the isolates of both strains of CGMMV. The virus accumulated also in C. myriocarpus and the European isolate produced symptoms, but the Asian isolate did not. Thirty C. melo accessions were susceptible to CGMMV. An isolate-dependent expression of symptoms was observed in 16 melon accessions: they showed mild and severe symptoms at 14 and 21 days after inoculation with the European and Asian isolate, respectively. Freeman’s Cucumber showed few or no symptoms following inoculation with the isolate of either CGMMV strain. This particular accession also showed reduced virus accumulation, whereas most other tested germplasm accessions showed significantly higher viral loads and, therefore, may well be a candidate for breeding programs aiming to reduce the losses produced by CGMMV with resistant commercial melon cultivars.